Interagency Trust and Communication in the Transboundary Governance of Pacific Salmon Fisheries. Issue 1 (January 2015) - Temby, Owen; Rastogi, Archi; Sandall, Jean; Cooksey, Ray; Hickey, Gordon M.
Abstract The transboundary governance of Pacific salmon fisheries requires interactions between institutions that can enable collective action, collaboration, and continuous learning. However, relatively little is known concerning how civil servants in different institutions and jurisdictions interact with each other within transboundary policy settings. In this paper, we explore the interactions of civil servants from agencies in five jurisdictions: United States (federal), Canada (federal), British Columbia, Yukon, and Alaska, to assess the extent to which they interact within the Pacific salmon policy network and also the social capital (i.e., formal and informal communication and trust) present among these working relationships. Our results reveal patchy patterns of interagency communication, and relatively low levels of interagency trust between jurisdictions, suggesting the potential for improved collaboration on Pacific salmon governance. Our analysis also revealed that the binational Pacific Salmon Commission had the highest levels of trust within the network, suggesting it is likely well placed to foster collaboration.